Perspectives on using integrated tick management to control Rhipicephalus microplus in a tropical region of Mexico - Lagunes-Quintanilla, Rodolfo; Gómez-Romero, Ninnet; Mendoza-Martínez, Nancy; Castro-Saines, Edgar; Galván-Arellano, Dulce; Basurto-Alcantara, Francisco Javier (Frontiers in Veterinary Science, 2024)
The Rhipicephalus microplus tick is widely recognized as the most economically significant ectoparasite affecting cattle globally, particularly in the Neotropical region. In Mexico, at least 65% of the cattle are infested with R. microplus and are susceptible to tick-borne diseases. Integrated tick management strategies are required to maintain compatible levels of animal production and reduce the reliance on chemical acaricides for tick control. Therefore, this paper aims to analyze current methods for controlling tick infestation in extensively raised cattle using Integrated Tick Management (ITM) and to propose an ITM program suitable for implementation in the humid tropical region of Veracruz, Mexico.